2015
DOI: 10.1016/j.jiph.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Trends and variations in the epidemiology of meningococcal disease in Kuwait 1987–2013

Abstract: The introduction of Haemophilus influenzae type b (Hib) conjugate vaccine and conjugate pneumococcal vaccine into routine childhood vaccination in Kuwait has resulted in the emergence of Neisseria meningitidis as the leading cause of invasive bacterial infection in children. Currently, a quadrivalent ACYW-135 meningococcal polysaccharide vaccine is administered as part of routine childhood vaccination in Kuwait at the age of 2 years. Conjugate meningococcal vaccines have been shown to be more effective in prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Serogroup B accounted for 34% of all cases in children ≤ 14 years, and serogroup A accounted for 40% of all adult cases. Three outbreaks in Kuwait in 1987, 1989, and 2002 were caused by serogroups A, W, and B, respectively [ 30 ].…”
Section: Global Epidemiology Of Invasive Meningococcal Disease In Tramentioning
confidence: 99%
“…Serogroup B accounted for 34% of all cases in children ≤ 14 years, and serogroup A accounted for 40% of all adult cases. Three outbreaks in Kuwait in 1987, 1989, and 2002 were caused by serogroups A, W, and B, respectively [ 30 ].…”
Section: Global Epidemiology Of Invasive Meningococcal Disease In Tramentioning
confidence: 99%
“…Of the 30 articles retrieved in the NM literature search, 8 were included in the analysis (2 publications each from Iran [33,34] and Turkey [35,36] and single publications from Egypt [37], Kuwait [38], Saudi Arabia [39], and Yemen [40]) (Fig. 1; Table 2).…”
Section: Neisseria Meningitidismentioning
confidence: 99%
“…1; Table 2). Of the identified publications, two were based on national surveillance [38,39], with the remaining being smaller studies (e.g., hospital/school based) [33][34][35][36][37]. Five studies reported on disease epidemiology [33,[37][38][39][40] and three on carriage epidemiology [34][35][36] for NM among adults in MENA.…”
Section: Neisseria Meningitidismentioning
confidence: 99%
See 1 more Smart Citation
“…Kuwait occupies an area of just under 18,000 square kilometres at the tip of the Arabian Gulf and has a population of 4 million. The Kuwaiti Ministry of Health (MOH) is the major provider of healthcare, although in recent years there has been an emerging contribution from private healthcare clinics [ 17 ].…”
Section: Regional Considerationsmentioning
confidence: 99%